Performance of Cementless Hip Arthroplasty Stem Types Based on Consolidated Large Registry Data - Logan E. Finger, MD; Matthew F. Gong, MD; Asher Mirvish, BS; Alexandra S. Gabrielli, MD; Ahmad P. Tafti, PhD; Michael J. O’Malley, MD; Brian A. Klatt, MD; Johannes F. Plate, MD, PhD (Arthroplasty Today)
Background: Improvements in cementless total hip arthroplasty have been directed at optimizing osseointegration of the femoral implant to reduce aseptic loosening rates. Stem design plays a critical role in the performance of these implants. Given the increase in new stem designs and the creation of an updated classification system, improved understanding of the outcomes of each stem type is warranted. The purpose of this study was to determine overall revision rates based on stem design and proprietary model. Methods: Joint registry data on the reported overall cases and revisions for each cementless stem brand were collected from the annual reports of the American Joint Replacement Registry (2021), United Kingdom National Joint Registry (2021), New Zealand Joint Registry (2020), and Australian Orthopaedic Association National Joint Replacement Registry (2021). Each individual stem brand was classified into a stem type derived from the classification system described by Radaelli et al. Results: The most utilized stem types were (1) type B2 stems, (2) type A stems, and (3) type C1 stems. The most utilized stem models were the (1) Corail stem (B2), (2) Accolade II (type A), and (3) Taperloc 133 (type A). The highest and lowest overall revision rates observed were in the type B1 stems (8.09%) and type C3 stems (1.12%), respectively. The 3 stem models with the highest overall revision rates were the Synergy HA stem (9.04%), CBC stem (8.59%), and CLS stem (7.96%). The 3 stems with the lowest respective overall revision rates were the C2 stem (0.00%, 0 of 933 cases), Actis Duofix (0.59%), and VerSys stem (0.89%). Conclusions: Based on consolidated large registry data, some cementless femoral stem types and models appear to perform better than others when compared on the basis of stem design.